Symptoms of Flat Feet and Pimples in Children (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Flat feet is a common musculoskeletal deformity in children, characterized by the collapse or flattening of the foot arches. This condition may be congenital or acquired due to weak muscles, ligament laxity, or improper footwear. Children with flat feet often experience pain in the feet, ankles, or legs, rapid fatigue during walking, and changes in posture and gait. Early diagnosis and timely treatment through orthopedic correction, physiotherapy, and exercise are crucial for preventing long-term complications.In addition, pimples (juvenile acne) are frequently observed in children and pre-adolescents as a result of hormonal changes, poor hygiene, or dietary factors. Although generally mild, untreated cases may lead to skin irritation, inflammation, and psychological discomfort. The paper discusses the main causes, symptoms, and diagnostic approaches for both conditions, emphasizing preventive measures and proper care. The integration of orthopedic and dermatological health education can significantly improve the overall physical and emotional well-being of children.